Evaluating Commercial Control Materials and Homemade Lyophilisates Quality in Kidney Function Test with Sigma Metric - Alifa Christin; Anik Handayati (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
This study aims to determine the quality of commercial control materials and homemade lyophilisates using the sigma metric method for BUN and creatinine parameters in a primary clinical laboratory. This cross-sectional study conducted 20 examinations on both types of control materials. The results showed that for the BUN parameter, homemade lyophilisates had a sigma value of 1 (unacceptable), while the commercial control material had a sigma value of 2 (poor). For the creatinine parameter, both homemade lyophilisates and commercial control materials had a sigma value of 3 (marginal). There was a significant difference in quality between commercial control materials and homemade lyophilisates for the BUN parameter, so homemade lyophilisate cannot be used as an alternative to commercial control materials. However, for the creatinine parameter, there was no significant difference in quality between the two control materials, so homemade lyophilisates can be used as an alternative to commercial control materials. Thus, this study shows that homemade lyophilisates can be an effective and economical alternative for creatinine parameters, but not for BUN parameters. This research can help primary clinical laboratories to develop more effective and efficient quality control strategies.